The rebounders : a Division I basketball journey - Ottaway, Amanda (University of Nebraska Press, 2018)
"Unlike the stories of most visible Division I college athletes, Amanda Ottaway's story has more in common with those of the 80 percent of college athletes who are never seen on TV. The Rebounders follows the college career of an average NCAA Division I women's basketball player in the twenty-first century, beginning with the recruiting process when Ottaway is an eager, naive teenager and ending when she's a more contemplative twentysomething alumna. Ottaway's story, along with the journeys of her dynamic Wildcat teammates at Davidson College in North Carolina, covers in engaging detail the life of a mid-major athlete: recruitment, the preseason, body image and eating disorders, schoolwork, family relationships, practice, love lives, team travel, game day, injuries, drug and alcohol use, coaching changes, and what comes after the very last game. In addition to the everyday issues of being a student athlete, The Rebounders also covers the objectification of female athletes, race, sexuality, and self-expression. Most college athletes, famous or not, play hard, get hurt, fail, and triumph together in a profound love of their sport and one another, and then their careers end and they figure out how to move on. From concussions and minor injuries to classrooms, parties, and relationships, Ottaway understands the experience of a Division I women's basketball player firsthand. The Reboundersis, at its core, a feminist coming-of-age story, an exploration of what it means to be a young woman who loves a sport and is on a course of self-discovery through that medium."--